Analisis Faktor Determinan Status Gizi Balita: A Systematic Review - Sembiring, Anita Christina (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Introduction: As the future generation of the nation, child health must receive special attention. Nutritional problems in children continue to be a major public health issue worldwide. There are 149.2 million children under five years old experiencing stunting; 45.4 million children are underweight, and 38.9 million children are overweight. Malnutrition remains a critical public health issue for children under five years old in developing countries. Various studies indicate that the factors associated with nutritional problems in children vary from country to country. Objective: This study aims to identify factors related to nutritional status in young children. Method: This research employs a systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Article searches were conducted using three databases: PubMed, ScienceDirect, and Scopus. The inclusion criteria for this study were articles published between 2013 and 2023 and available in open access, with the sample consisting of young children. Results: A review of 22 articles revealed that the determinants of young children's nutritional status include parental characteristics such as maternal education, maternal occupation, maternal age, maternal BMI, and maternal knowledge; family characteristics including the number of children and family socioeconomic status; disease factors such as diarrhea and low birth weight; and hygiene and sanitation factors including access to clean water, toilets, and healthcare facilities. Conclusion: Nutritional status in young children can be influenced by education, economic conditions, hygiene practices, and healthcare facilities.